World Trade Organisation members' compliance with article XXIV of the General Agreement on Tariffs and Trade : The case of Tanzania - Oluyeju, Femi (University of Pretoria, 2021)
Mini Dissertation (LLM (International Trade and Investment Law in Africa))--University of Pretoria, 2021.